Política curricular, crisis de legitimación y hegemonía neoliberal: Una visión desde la sociología de la educación crítica - Miranda Camacho, Guillermo (Universidad de Costa Rica, 2022)
In this article, we intend a hermeneutical approach, from the sociology of critical education, to analyze the role that curricular policies and t official knowledge play in the configuration process of the hegemonic neoliberal system, which took place as a result of the crisis of legitimacy of regulated capitalism and the Welfare State. The article is structured around the following thematic nucleus: a) the role of curriculum in the legitimacy crisis based on Habermas and Offe’s theory of legitimacy; b) the alliance between neoconservatives and neoliberals and the upcoming neoliberal hegemony in education; c) its strategy of legitimacy as a beginning of the connection between official knowledge and neoliberal curricular policies; d) the curriculum as ideology in the context of the neoliberal hegemony in education and its search for universal validation; and e) a hermeneutical critical approach to the sociopolitical and ideological nature of the curriculum, in which we introduce two concepts to the analysis: explicit teleology and concrete teleology.